2019
DOI: 10.1186/s12935-019-0856-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cold atmospheric plasma treatment on the metabolites of human leukemia cells

Abstract: Background Acute myeloid leukemia (AML) is a typically fatal malignancy and new drug and treatment need to be developed for a better survival outcome. Cold atmospheric plasma (CAP) is a novel technology, which has been widely applied in biomedicine, especially in various of cancer treatment. However, the changes in cell metabolism after CAP treatment of leukemia cells have been rarely studied. Methods In this study, we investigated the metabolite profiling of plasma tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 35 publications
1
22
0
Order By: Relevance
“…This results in intermediate metabolites that tumorous cells can use for growth and proliferation [116][117][118]. Xu et al [119] studied CAP effects on altered cancer cell metabolic activity. Their KEGG and GC-TOFMS analyses highlighted that leukaemia cells had different alanine, aspartate, and glutamate metabolism.…”
Section: Use Of Cap For Tumour Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…This results in intermediate metabolites that tumorous cells can use for growth and proliferation [116][117][118]. Xu et al [119] studied CAP effects on altered cancer cell metabolic activity. Their KEGG and GC-TOFMS analyses highlighted that leukaemia cells had different alanine, aspartate, and glutamate metabolism.…”
Section: Use Of Cap For Tumour Treatmentmentioning
confidence: 99%
“…This decreases the conversion of glutamine to glutamic acid. Deficiency of Glutamic acid, simultaneously with glutamine accumulation can lead to suppression of proliferation and even cell death in leukemia cells [119].…”
Section: Use Of Cap For Tumour Treatmentmentioning
confidence: 99%
“…Various signaling effects were altered on CAP‐induced apoptosis in different studies. We have previously shown that CAP can selectively induce the apoptosis of triple‐negative breast cancer cells both in vitro and in vivo by suppressing the phosphorylation level of JNK [ 17 ] and proposed the use of “cell number,” “treatment time,” “area,” and “depth” as key parameters controlling CAP dose through the establishment of a linear model from an orthogonal experimental design. [ 16 ] CAP was lately shown to induce apoptosis in melanoma cells via sestrin2‐mediated nitric oxide synthase signaling [ 33 ] and by targeting the HGF/c‐MET downstream pathway.…”
Section: Dose‐dependent Oncotherapeutic Effects Of Plasmamentioning
confidence: 99%
“…The selectivity of CAP on cancer cells has been reported in various types of cancer cells such as triple‐negative breast cancer, [ 17 ] melanoma, [ 33,34 ] non‐small‐cell lung cancer, [ 42 ] head and neck carcinoma, [ 15 ] and pancreatic cancer [ 13 ] (Table 1). It was stated that malignant cells have higher baseline ROS levels than normal cells due to elevated ROS creation and inefficient redox scavenging.…”
Section: Opportunities For Precision Plasma Dosementioning
confidence: 99%
See 1 more Smart Citation